Does an observer's empathy influence my pain? Effect of perceived empathetic or unempathetic support on a pain test. (19th October 2017) - Fauchon, C.; Faillenot, I.; Perrin, A. M.; Borg, C.; Pichot, V.; Chouchou, F.; Garcia‐Larrea, L.; Peyron, R.
Abstract: The physiological and behavioural effects of empathy for other's pain have been widely investigated, while the opposite situation, i.e. the influence on one's pain of empathetic feedback from others, remains largely unexplored. Here, we assessed whether and how empathetic and unempathetic comments from observers modulate pain and associated vegetative reactions. In Study 1, conversations between observers of a pain study were recorded by professional actors. Comments were prepared to be perceived as empathetic, unempathetic or neutral, and were validated in 40 subjects. In a subsequent pain experiment (Study 2), changes in subjective pain and heart rate were investigated in 30 naïve participants who could overhear the empathetic or unempathetic conversations pre‐recorded in study 1. Subjective pain was significantly attenuated when hearing empathetic comments, as compared to both unempathetic and neutral conditions, while unempathetic comments failed to significantly modulate pain. Heart rate increased when hearing unempathetic remarks and when receiving pain stimuli, but heart acceleration to nociceptive stimulation was not correlated with pain ratings. These results suggest that empathetic feedback from observers has a positive influence on pain appraisal and that this effect may surpass the negative effect of unempathetic remarks. Negative remarks can either trigger feelings of guilt or induce irritation/anger, with antagonistic effects on pain that might explain inter‐individual variation. As in basal conditions heart rate and pain perception are positively correlated, their dissociation here suggests that changes in subjective pain were linked to a cognitive bias rather than changes in sensory input. Abstract : It is commonly assumed that receiving empathetic feedback from others can reduce pain, but this postulate has received little experimental support so far. Here we provide experimental evidence that an empathetic context can significantly decrease the subjective perception of pain intensity as compared to a neutral or an unempathetic environment. Pain stimulations and unempathetic comments induced an increase in cardiac activity.